2023
DOI: 10.1002/vms3.1235
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum 25(OH) vitamin D, parathormone and immunity marker concentrations between dogs with transmissible venereal tumour and healthy dogs

Abstract: Background1,25‐Dihydroxyvitamin D (1,25(OH)2 D) is vital in the homeostasis of calcium and bone health as well as in the prevention of many disorders such as neoplasms. Epidemiological data show that low concentrations of both 1,25(OH)2D and its precursor 25(OH) vitamin D (25(OH)D) are associated with an increased risk of a variety of human tumours.ObjectivesTo investigate 25(OH)D, parathormone (PTH) and immunity marker concentrations in dogs with transmissible venereal tumour (TVT).Methods25(OH)D, PTH and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Afterward, PTH stimulates 1alpha‐hydroxylase activity, ultimately increasing calcitriol synthesis with a subsequent increase in intestinal calcium and phosphorus absorption. 7 However, in our study, reduced vitamin D concentrations were not observed. Parathyroid hormone could also have a direct influence on the biology of breast tumors.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Afterward, PTH stimulates 1alpha‐hydroxylase activity, ultimately increasing calcitriol synthesis with a subsequent increase in intestinal calcium and phosphorus absorption. 7 However, in our study, reduced vitamin D concentrations were not observed. Parathyroid hormone could also have a direct influence on the biology of breast tumors.…”
Section: Discussioncontrasting
confidence: 81%
“…The present study did not support any association between lower 25‐hydroxyvitamin D concentrations and mammary cancer in bitches as has been demonstrated in dogs with other types of neoplasia. 4 , 5 , 6 , 7 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations